PENGARUH KEBIJAKAN DIVIDEN, KINERJA KEUANGAN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan Manufaktur di BEI Periode 2017-2020) - Adinda Winadianti Ramadhan; Rukmini Rukmini; LMS Kristiyanti (ITB AAS INDONESIA, 2023)
This study aims to determine the effect of dividend policy, financial performance, and firm size on firm value. This type of research is quantitative research by testing the hypothesis. The sample collection procedure in this study used a purposive sampling technique with a total sample of 84 manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The analytical method used is descriptive statistics and classical assumption test with hypothesis testing including: multiple linear regression, F test, t test, and coefficient of determination test. The results showed that financial performance (ROA) had a significant effect on firm value (PBV), while dividend policy (DPR) and firm size (SIZE) had no effect on firm value (PBV). Simultaneously shows that dividend policy (DPR), financial performance (ROA), and firm size (SIZE) have an effect on firm value (PBV).